2020
DOI: 10.3389/fnins.2020.00185
|View full text |Cite
|
Sign up to set email alerts
|

Altered Patterns of Phase Position Connectivity in Default Mode Subnetwork of Subjective Cognitive Decline and Amnestic Mild Cognitive Impairment

Abstract: Alzheimer's disease (AD), which most commonly occurs in the elder, is a chronic neurodegenerative disease with no agreed drugs or treatment protocols at present. Amnestic mild cognitive impairment (aMCI), earlier than AD onset and later than subjective cognitive decline (SCD) onset, has a serious probability of converting into AD. The SCD, which can last for decades, subjectively complains of decline impairment in memory. Distinct altered patterns of default mode network (DMN) subnetworks connected to the whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The brain areas of the SN were summarized as follows: (1) Use ICA: bilateral anterior insula (Yi et al, 2015 ), bilateral frontoinsular cortex, bilateral anterior cingulate cortex (ACC) (Han et al, 2011 ), bilateral dorsal ACC (dACC), bilateral insula lobule (Chand et al, 2017 ), right supplementary motor area (SMA), left superior temporal gyrus (STG), bilateral supramarginal gyrus (SG), left precuneus (Conwell et al, 2018 ; Cai et al, 2020b ), preSMA (Yi et al, 2015 ), dorsal anterior cingulate cortex/medial prefrontal cortex (dACC/MPFC), dorsolateral prefrontal cortex (DLPFC) (He et al, 2014 ), bilateral caudate (Agosta et al, 2012 ), the thalamus (Wang et al, 2020 ), bilateral ventrolateral prefrontal cortex, bilateral STG/insula, midcingulate cortex/preSMA, medial orbitofrontal cortex, and bilateral orbital/frontoinsular (Agosta et al, 2012 ) and (2) Use seed ROI: bilateral frontoinsular cortex (Joo et al, 2017 ), bilateral anterior insula, bilateral dACC, dACC/MPFC, bilateral anterior insula (Zhu et al, 2016 ), bilateral insula (Sarli et al, 2021 ), and bilateral SG (Liang et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…The brain areas of the SN were summarized as follows: (1) Use ICA: bilateral anterior insula (Yi et al, 2015 ), bilateral frontoinsular cortex, bilateral anterior cingulate cortex (ACC) (Han et al, 2011 ), bilateral dorsal ACC (dACC), bilateral insula lobule (Chand et al, 2017 ), right supplementary motor area (SMA), left superior temporal gyrus (STG), bilateral supramarginal gyrus (SG), left precuneus (Conwell et al, 2018 ; Cai et al, 2020b ), preSMA (Yi et al, 2015 ), dorsal anterior cingulate cortex/medial prefrontal cortex (dACC/MPFC), dorsolateral prefrontal cortex (DLPFC) (He et al, 2014 ), bilateral caudate (Agosta et al, 2012 ), the thalamus (Wang et al, 2020 ), bilateral ventrolateral prefrontal cortex, bilateral STG/insula, midcingulate cortex/preSMA, medial orbitofrontal cortex, and bilateral orbital/frontoinsular (Agosta et al, 2012 ) and (2) Use seed ROI: bilateral frontoinsular cortex (Joo et al, 2017 ), bilateral anterior insula, bilateral dACC, dACC/MPFC, bilateral anterior insula (Zhu et al, 2016 ), bilateral insula (Sarli et al, 2021 ), and bilateral SG (Liang et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…The rs-fMRI data were preprocessed using the software MATLAB 2014a and Rs-fMRI Data Analysis Toolkit (REST; http://restfmri.net ) [ 46 ]. Preprocessing included the following steps: (1) The first ten time points were discounted to ensure stable-state longitudinal magnetization and to allow subjects acclimate to the scanning environment; (2) functional images were corrected for differences in image acquisition time between slices; (3) all the imaging data were realigned for head movement correction; (4) the participant’s anatomical images were segmented, and the deformation field maps were applied to the functional images to normalize them into the standard Montreal Neurological Institute (MNI) space, with a resampled voxel of size 3 × 3 × 3 mm 3 [ 47 ]; (5) the functional volumes were spatially smoothed by means of an isotropic Gaussian kernel of 6 mm full-width at half-maximum.…”
Section: Methodsmentioning
confidence: 99%
“…The STGtp is an important component of the temporal lobe, located in front of STG, and participates in a variety of important cognitive functions ( 40 ). Studies have found that the patients with cognitive impairment had reduced STG cortical thickness and increased neural activity compared with normal subjects ( 41 43 ). Besides, a recent neuroimaging meta-analysis of PIU has shown that STG was hyperactivated in the executive control tasks, suggesting that STG was involved in the executive control function of the subjects with PIU ( 24 ).…”
Section: Discussionmentioning
confidence: 99%